Medical hypnosis on depression and interleukin-6 levels in lung cancer patients - Kusuma, Wijaya; Andriatno, Ardi; Seno, Budhi Hami (International Journal of Research in Medical Sciences, 2024)
Background: Lung cancer patients are at high risk for depression, which is associated with poor treatment adherence. Medical hypnosis can improve symptoms of depression and affect interleukin-6 levels. This study aims to determine the effectiveness of medical hypnosis in improving depression and reducing IL-6 levels in lung cancer patients. Methods: This study is a quasi-experimental study with a pretest and post-test control group design. It assessed depressive symptoms using BDI-II scores and serum IL-6 levels in an intervention group receiving medical hypnosis and standard therapy compared to a control group receiving standard therapy. Data analysis was conducted using univariate tests, followed by Pearson correlation tests and effect size measurement with Cohen's d test. Results: The Wilcoxon test showed a decrease in IL-6 levels in the intervention group by 14.66±19.45 (p=0.008) and a reduction in BDI-II scores by 8.26±4.78 (p=0.001). Correlation tests indicated a significant relationship between IL-6 levels and BDI-II scores (r=0.472; p=0.009). Cohen's d test showed the effect size of medical hypnosis on IL-6 levels was 0.754 (moderate=0.5<ES<0.8). Conclusions: Medical hypnosis is effective in improving depressive symptoms and reducing IL-6 levels in lung cancer patients.